Vibrio interactions with bivalve hemocytes and analysis of the Crassostrea gigas microbiota - BORELLO, ALESSIO (Università degli studi di Genova, 2021)
My PhD project aimed at investigating the molecular mechanisms at the basis of the interaction between Vibrio bacteria and shellfish in the bivalve models Crassotrea gigas and Mytilus galloprovincialis and to study the composition and dynamics of bivalve microbiota. Previous studies suggested that persistence of entrapped bacteria inside bivalve tissues depends, at least in part, on their capacity to survive to the hemolymph bactericidal activity, that is exerted by both hemocytes and serum soluble factors. In the first part of my PhD work, hemocytes of M. galloprovincialis were challenged with different pathogenic Vibrio strains (V. aestuarianus 01/032, V. aestuarianus 02/041, V. tasmaniensis LGP32, V. harveyi VH2, V. tapetis CECT 4600 and V. coralliilyticus ATCC BAA 450) in the presence or in the absence of the extrapallial protein present in M. galloprovincialis serum (MgEP), and of the whole hemolymph serum. In addition, C. gigas hemocytes were exposed to the bivalve pathogens V. aestuarianus 01/032 and V. aestuarianus 02/041 under the same conditions to better understand molecular basis of bacteria-hemolymph interactions in oysters. We observed that MgEP promotes D- mannose sensitive adhesion to and killing by hemocytes of the bivalve pathogens V. aestuarianus 01/032, V. aestuarianus 02/041, V. tasmaniensis LGP32 and V. coralliilyticus ATCC BAA 450. In addition, in the presence of M. galloprovincialis EP protein (MgEP), C. gigas haemocytes killed V. aestuarianus 01/032 and V. aestuarianus 02/041 almost as efficiently as mussel phagocytes. These findings suggest that the different sensitivity of Vibrio strains to the antibacterial activity of oyster (susceptible to Vibrio infection) and mussel (resistant to Vibrio infection) haemolymph might partly depend on the fact that C. gigas serum lacks MgEP-like opsonins. These results may have important implications for improving bivalve depuration strategies and prevent diseases affecting bivalve production worldwide. In the second part of my thesis work, I studied ...